PELAKSANAAN PEMBANGUNAN DI DESA RAMBAH TENGAH HULU KECAMATAN RAMBAH KABUPATEN ROKAN HULU TAHUN 2009-2013 - Mahendra "; Raja Muhammad Amin (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2016)
The problem in this research is how the implementation of the development in the Village Middle Rambah Rambah Hulu District of Rokan Hulu in the year 2009-2013 and the factors inhibiting the implementation of the development in the Village Middle Rambah Rambah Hulu District of Rokan Hulu. Implementation of village development Rambah Central Hulu, the authors noticed there is still potential to be managed premises well, so it will give more support rural incomes and for equitable development can be achieved, which is still the wealth of the village in the form of land which can be used and managed by the village government and with the community ,The purpose of this is to determine the factors that affect the implementation of development in the village of Central Rambah Rambah Hulu District of Rokan Hulu. With the research methods used in this study is a qualitative research data collection techniques used is by using the technique of observation, interview and documentation.The results of this study, that the Government Rural Middle Rambah Hulu in conducting village development is influenced by several factors, namely; factor of personnel resources of the village, the source of funding factors, factors of community participation and community motivation factor. Village Middle Rambah Hulu is still not able to optimize the three elements of development, namely; government, public and private, and the authors suggest to the Government of Hulu's Village Central Rambah that would improve the ability of village officials and good communication in carrying oriented government on regional autonomy.Keywords: Human Resources, Funding, Community Participation and Motivation